Textual Features of Perbilangan: (Ciri Tekstual Perbilangan) (Jurnal Bahasa, 2018)
Malay sayings, or perbilangan, are a type of language act which represent certain messages, customs, rules, and values as guidelines for society. These are figurative and indirect expressions in stanzaic form. In this article, the textual features of perbilangan will be described. Employing the internal textual analysis approach, which focuses on the organization of texts in their entirety, clause combinations, clause categories, and the nature of the sayings themselves, and aided by functional grammar, the analysis of a corpus of sayings related to the Malay value system, kinship, politics, financial issues, customs, and social strata reveals several textual features of perbilangan. Most of these features have never been discussed before. The findings show that perbilangan are a unique language act. Their uniqueness lies in their textual features, and not so much in embedded values or messages. Values or messages may be presented in more direct ways in everyday expressions. The textual features of perbilangan also differentiate these from other language acts or traditional Malay poems. It is these textual features by which messages or values can be conveyed more effectively, politely and indirectly, indicating the high degree of refinement of Malay culture.Key words: sayings, textual features, internal textual analysis, values, messages, rules, customs